Urmila: Revealing the Power of an Exceptional Woman in Kavita Kane’s ’Sita’s Sister’ - M., Sarada Devi; Bhanu Shaik, Shakila (International Journal of Psychosocial Rehabilitation, 2020)
The study explores the marginalization of women in Indian epics, particularly focusing on Urmila in the Ramayana. Traditionally, epics like the Ramayana and Mahabharata depict women as subjugated in a patriarchal society, influencing both individual and societal values. The 20th century, marked by advances in science and technology, allowed women to break free from traditional domestic roles and assume prominent societal positions. Female authors began reinterpreting these ancient texts, reshaping stories to emphasize women’s empowerment and responsibilities. This paper specifically examines Urmila’s overlooked role in the Ramayana, and how feminist perspectives, like those in Kane’s reinterpretation, shed light on the potential for redefining women’s roles in contemporary adaptations of these myths.